2021
DOI: 10.3390/math10010083
|View full text |Cite
|
Sign up to set email alerts
|

Multi-UAV Coverage Path Planning Based on Hexagonal Grid Decomposition in Maritime Search and Rescue

Abstract: In the event of a maritime accident, surveying the maximum area efficiently in the least amount of time is crucial for rescuing survivors. Increasingly, unmanned aerial vehicles (UAVs) are being used in search and rescue operations. This study proposes a method to generate a search path that covers all generated nodes in the shortest amount of time with multiple heterogeneous UAVs. The proposed model, which is a mixed-integer linear programming (MILP) model based on a hexagonal grid-based decomposition method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Thomas et al proposed a novel metamodel to estimate the mission success possibility for a SAR task with the support of a supervised learning method [28]. Similar studies can be found in [29][30][31]. We find that the particle swarm optimization (PSO) method is commonly used to determine the optimization deployment strategy of maritime rescue facilities.…”
Section: Introductionmentioning
confidence: 58%
“…Thomas et al proposed a novel metamodel to estimate the mission success possibility for a SAR task with the support of a supervised learning method [28]. Similar studies can be found in [29][30][31]. We find that the particle swarm optimization (PSO) method is commonly used to determine the optimization deployment strategy of maritime rescue facilities.…”
Section: Introductionmentioning
confidence: 58%
“…Grid-based approaches [9][10][11][12][13][14][15][16][17][18] mainly divide the area into sub-areas to solve dynamic area coverage problems. In [9], Choset presented a strategy dividing the space into cell regions covered with back-andforth motions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies in [10][11][12] use multiple vehicles that focused on partitioning the area into sub-areas and then each sub-area assigned to a vehicle. Cho et al [13] proposed a method which creates a search path to cover an area. A mixed-integer linear programming (MILP) model has been used to determine a coverage path planning for visiting all generated nodes in the shortest amount of time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, because of their excellent mobility and high flexibility, UAVs can operate in hazardous environments or in places that are inaccessible to people or ground-based equipment, such as during forest fires or search-and-rescue operations in the water. Uncertainty in search and rescue is somewhat diminished by the UAVs' operational effectiveness [82]. The UAVs can conduct a thorough search in a short amount of time thanks to their air superiority and information transmission capabilities.…”
Section: Seek and Rescuementioning
confidence: 99%